Avaliação de métodos de estimação fasorial para uso na proteção de distância em linhas com compensação série - Chaves, Thalita Faheina (Universidade Federal Rural do Semi-Árido, 2019)
This work aims to evaluate phasor estimation methods applied in transmission lines with series compensation, used in numerical relays for distance protection in transmission lines. Comparisons were made between five phasor estimation algorithms: Full Cycle Discrete Fourier Transform (FDFT), Modified Cosine, Digital Mimic Filter with FDFT, Guo Algorithm and the algorithm developed by CAMPOS (2016). In the first part of this work, analytical signals containing undesirable components were generated, using MATrix LABoratory software (MATLAB®). The phasor estimation methods were evaluated using performance indexes. For one of the signals, containing subharmonic and decaying DC components, the Campos method presented better results, with lower values in 78% of the cases for the index that quantifies the oscillation of the response in time and in 100% of the cases for the index that quantifies the percentage of overshoot, while the FDFT method was the one that had the worst result and was more susceptible to the subharmonic frequencies. Regarding the index that quantifies the speed of convergence in the phasor estimation, the combination of the mimic filter with FDFT method presented lower mean values. Then, a database was created, obtained through the modeling of a transmission line with series compensation and fault simulation using Alternative Transients Program (ATP) software. The location of the series capacitor banks, the degree of compensation, incidence angle and fault type location were varied, totaling 288 cases. The results obtained in the ATP were used as input signals for the MATLAB®, where the autopolarized MHO type distance relay was modeled and where the phasor estimation algorithms extracted the fundamental voltage and current components. In the analysis of the results, the performance of the algorithms was compared through the apparent impedance trajectory, number of cycles required for fault distance estimation and tripping time. In conclusion of this comparison, it is observed that all algorithms are affected by the unwanted components introduced by the presence of series compensation in the line, since there is a reduction in the value of the apparent impedance that can cause a protection malfunction
Keywords: Linhas de transmissão; Métodos de estimação fasorial; Compensação série; ATP; MATLAB®; Transmission lines; Phasor estimation methods; Series compensation; ATP; MATLAB®; ENGENHARIAS::ENGENHARIA ELETRICA